2015
DOI: 10.1021/acs.jafc.5b01165
|View full text |Cite
|
Sign up to set email alerts
|

Kiwifruit Flower Odor Perception and Recognition by Honey Bees, Apis mellifera

Abstract: Volatile organic compounds (VOCs) from male and female kiwifruit (Actinidia deliciosa 'Hayward') flowers were collected by dynamic headspace sampling. Honey bee (Apis mellifera) perception of the flower VOCs was tested using gas chromatography coupled to electroantennogram detection. Honey bees consistently responded to six compounds present in the headspace of female kiwifruit flowers and five compounds in the headspace of male flowers. Analysis of the floral volatiles by gas chromatography-mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
(86 reference statements)
1
18
0
Order By: Relevance
“…Some compounds, although normally emitted also by healthy and vegetative tissues [52], were differentially released from control and inoculated flowers, suggesting that odour signals may drive honeybees foraging preferences. According to previous studies [53][54][55], honeybees respond to a small subset of total floral VOCs, several of which were observed in this work: benzaldehyde, (E)-βocimene, linalool, nonanal, methyl salicylate, (E,E)-α-farnesene, phenylethyl alcohol and 2-phenylethyl acetate. In this study, (E,E)-α-farnesene was one of the most strongly emitted compounds, and showed a dramatic surge after infection; other sesquiterpenes (copaene, (-)-β-bourbonene, (E)-caryophyllene, ledene, curcumene and farnesene isomers) followed the same trend.…”
Section: Plant-pollinator Relations Mediated By Vocssupporting
confidence: 67%
“…Some compounds, although normally emitted also by healthy and vegetative tissues [52], were differentially released from control and inoculated flowers, suggesting that odour signals may drive honeybees foraging preferences. According to previous studies [53][54][55], honeybees respond to a small subset of total floral VOCs, several of which were observed in this work: benzaldehyde, (E)-βocimene, linalool, nonanal, methyl salicylate, (E,E)-α-farnesene, phenylethyl alcohol and 2-phenylethyl acetate. In this study, (E,E)-α-farnesene was one of the most strongly emitted compounds, and showed a dramatic surge after infection; other sesquiterpenes (copaene, (-)-β-bourbonene, (E)-caryophyllene, ledene, curcumene and farnesene isomers) followed the same trend.…”
Section: Plant-pollinator Relations Mediated By Vocssupporting
confidence: 67%
“…studied Brassicaceae, and oilseed was investigated by Pham‐Delègue and colleagues . Recently, four compounds have been identified as the key bioactive compounds that honey bees recognise in kiwifruit flowers, representing only part of the floral bouquet . Here we focus only on honey bees which are used worldwide for their pollination services, but additional volatiles may be important for attracting other pollinators …”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Recently, four compounds have been identified as the key bioactive compounds that honey bees recognise in kiwifruit flowers, representing only part of the floral bouquet. 32 Here we focus only on honey bees which are used worldwide for their pollination services, but additional volatiles may be important for attracting other pollinators. 33,34 In this study, we investigated the floral scent from three hybrid crops grown in New Zealand for seed production: carrot (Daucus carota), radish (Raphanus sativis) and Chinese cabbage (syn.…”
Section: Introductionmentioning
confidence: 99%
“…Among flower volatile compounds, lilac aldehyde is highly attractive to pollinators (e.g., Lepidoptera) and is emitted in high amounts in nocturnal plant species [16]. Twidle et al [17,18] found that certain volatiles of both A. chinensis varieties are recognized by honey bees and bumble bees. Then, apart from the flowers' appearance and the number of stamens, the composition of volatile compounds in flowers is also an interesting subject.…”
Section: Introductionmentioning
confidence: 99%